Strategies for Instilling Islamic Educational Values to Strengthen Student Character at Madrasah Babul Mujahidin Bayan - Raden Sumiadi (Jurnal Ilmiah Mandala Education (JIME), 2026)
This study aims to analyze the strategies for instilling Islamic educational values as a means of strengthening student character at Madrasah Babul Mujahidin Bayan, Lombok. The research focuses specifically on the forms of strategies employed in character development at Madrasah Babul Mujahidin. This study utilizes a qualitative approach, specifically a case study design. Data collection techniques involved observation, in-depth interviews, and documentation, with the madrasah principal, teachers, and students serving as informants. The findings indicate that the strategy for instilling Islamic educational values is implemented through several approaches: habituation, role modeling, the integration of values into classroom instruction, and routine religious activities such as congregational prayers, Quran recitation, and moral guidance. Furthermore, character strengthening is reinforced through a religious madrasah culture and a supportive social environment. The implementation of these strategies contributes positively to student character formation, as evidenced by increased discipline, responsibility, courtesy, and religious observance. This study concludes that a strategy integrating formal instruction, habituation, and role modeling serves as the key to strengthening student character based on Islamic educational values..